Women's and Midwives' Perspectives on the Design of a Text Messaging Support for Maternal Obesity Services: An Exploratory Study. (26th July 2012) - Soltani, H.; Furness, P. J.; Arden, M. A.; McSeveny, K.; Garland, C.; Sustar, H.; Dearden, A.
Abstract : This study was aimed to explore women's and midwives' views on the use of mobile technology in supporting obese pregnant women with healthy lifestyle choices. A purposive sample of 14 women and midwives participated in four focus groups in Doncaster, UK. A content analysis of the transcripts from the first focus group led to the emergence of three main constructs with associated subcategories including Benefits ("modernising, " "motivating, " "reminding, " and "reducing" the sense of isolation), Risks and Limitations (possibility of "being offensive, " "creating pressure or guilt, " and "being influenced by mood"), and Service Delivery (making it "available to all pregnant women, " giving attention to the "message tone" and development of "message content"). They also suggested the use of other modalities such as web-based services for weight management during pregnancy. Based on the above results a text messaging service was developed and presented to the 2nd focus group participants who confirmed the positive views from the first focus group on the use of the text messaging as being supportive and informative. The participants also welcomed "women's engagement and choice" in deciding the content, timing and frequency of messages. The results informed the development of a text messaging service to support maternal obesity management. The implementation and acceptability of this service requires further investigation.